Magnetic Fe3O4-encapsulated VAN@MIL-101(Fe) with mixed-valence sites and mesoporous structures as efficient bifunctional water splitting photocatalysts. Issue 23 (5th June 2020) - Guo, Yuan; Feng, Chao; Qiao, Shanshan; Wang, Shixin; Chen, Tingxiang; Zhang, Li; Zhao, Yansong; Wang, Jide
Abstract : Fe3 O4 /VAN@MIL-101(Fe) with both mesoporous and mixed-valence Fe 3+ /Fe 2+ structures was controllably synthesized in the synthesis of MIL-101(Fe), and it was used as a bifunctional photocatalyst in photocatalytic water splitting. Abstract : Fe3 O4 /VAN@MIL-101(Fe) with both mesoporous and mixed-valence Fe 3+ /Fe 2+ structures was controllably synthesized in the synthesis of MIL-101(Fe), and it was used as a bifunctional photocatalyst in both oxygen evolution reactions (OERs) and hydrogen evolution reactions (HERs) of photocatalytic water splitting. By the reduction of auxiliary ligand vanillin (VAN) and the introduction of Fe3 O4, the mixed-valence Fe 3+ /Fe 2+ structure in Fe3 O4 /VAN@MIL-101(Fe) was obtained, which improves the band gap of the Fe 3+ reactive active center and increases the separation efficiency of photogenerated carriers. Owing to the partial difference in the structure between VAN and ligand terephthalic acid (H2 BDC), hierarchical porous and vacant structures were effectively improved in Fe3 O4 /VAN@MIL-101(Fe), which can induce more active sites to adsorb more water molecules and shorten the electron–hole migration distance to improve the transfer efficiency of photogenerated carriers. Therefore, Fe3 O4 /VAN@MIL-101(Fe) presents excellent photocatalytic activities for improving the O2 and H2 production rate up to 360 000 μmol g −1 h −1 and 584 μmol g −1 h −1, respectively. Meanwhile, Fe3 O4 /VAN@MIL-101(Fe) maintains the excellent catalytic activity in OERs and HERs after recycling for 5 times. Moreover, the introduction of magnetic Fe3 O4 nanoplates into Fe3 O4 /VAN@MIL-101(Fe) can make it easily recyclable by magnetic separation, which can maximize its performance.